Peningkatan Pelayanan Kesehatan yang Berkesinambungan Melalui Bridging Sistem Informasi Manajemen (SIMRS) dengan Icare BPJS - Junaidi, Ahmad; Wadisman, Cendra (Universitas Labuhanbatu, 2024)
Improving health services to the community is the responsibility of all health facilities throughout Indonesia. One aspect that health facilities must pay attention to is being able to provide sustainable health services by looking at the diagnosis history and drug therapy that has been given to patients. This requires a tool to be able to view the history. However, in conditions where patients receive health services at different clinics or hospitals, problems arise, such as (1) Doctors cannot see the history of diagnosis and drug therapy at other health facilities, (2) Errors may occur in the next disease assessment, (3) and medically psychologically it can hinder doctors in making a diagnosis because sometimes the information from the patient is incomplete or does not meet the elements of truth. Hospital Management Information Systems usually only record the history of services, diagnoses, medical procedures, drug therapy given at the hospital. To find out the history of patients at other hospitals, SIMRS needs to bridge with systems outside it. Namely the BPJS Information system. The BPJS system has provided a service that can be used by Health Facilities to view patient history at other health facilities that the patient has visited. The system is named Icare BPJS. By connecting the Hospital SIM with the Icare BPJS SIM, it is hoped that it will be able to provide continuous health services to patients and minimize errors in determining diagnoses, drugs to be given and other medical procedures.